Enforcement of Sharia Criminal Offences in Cyberspace: Challenges from Malaysian Legal Perspective - Suhaizad Saifuddin; Fatimah Yusro Hashim; Mohd Zamre Mohd Zahir; Asma Hakimah Ab Halim (Prophetic Law Review)
The enforcement of Sharia criminal law in Malaysia faces substantial challenges in the digital era, where technological advancements have blurred traditional legal boundaries. Certain Sharia criminal offences committed in cyberspace remain difficult to prosecute due to jurisdictional limitations, evidentiary constraints, and the absence of specific legal provisions. These challenges underscore a growing disconnect between the enforcement of Sharia criminal law and the rapid evolution of digital technologies. This article examines the enforcement of Sharia criminal offences in cyberspace from the Malaysian legal perspective and proposes practical legal solutions to bridge the identified gaps. Employing a qualitative and doctrinal methodology, data were gathered through library-based research, statutory analysis, a review of reported cases, and relevant newspaper reports. The data were analysed using content analysis and descriptive methods. In addition, a comparative approach was adopted to assess the extent to which evidentiary and procedural frameworks from the common legal system in Malaysia could be adapted to enhance the effectiveness of Sharia criminal enforcement. In response, this article recommends targeted legislative reforms to enhance the Sharia legal system's capacity to address cyber-related offences, thereby ensuring that the enforcement of Sharia criminal law remains relevant and effective in the context of modern technological developments.